Insight into nucleophilic fragmentation mechanisms by glutamic acid side chain in singly protonated glutathione and related peptidyl ions. Issue 3 (June 2020) - Fan, Liqun; Wang, Jinhu; Liu, Chunli; Shi, Tiesheng; Zhang, Xian-Man; Xia, Yanqing; Fan, Lina; Liu, Yang
Fragmentation mechanisms of the singly protonated glutathione ( γ -ECG) and its synthetic analogue peptides (ECG and PPECG) have been investigated by liquid chromatography tandem-mass spectrometry and theoretical calculations. In the mass spectra, similar fragmentation patterns were observed for γ -ECG and ECG, but a completely different one was found in the case of PPECG. The E–C amide bond cleavage is the predominant pathway for the fragmentation of γ -ECG and ECG, whereas the additional N -terminal prolyl residues in PPECG significantly suppress the E–C amide bond cleavage. Theoretical calculations reveal that the fragmentation efficiencies of the E–C bonds in the protonated γ -ECG and ECG are much higher than that in the protonated PPECG, being attributed to their lower barriers of the potential energy; clearly the introduction of two prolyl residues can increase substantially the potential energy barrier. In the proposed mechanism, the protonated E–C amide bonds in the three peptides are first weakened followed by a nucleophilic addition by the glutamyl carboxyl oxygen atom in side chain, leading to the breaking of the E–C amide bonds. However, the processes of E–C bond fragmentation for three protonated analogs were not collaborative. Protonated amide bonds first fragment, then the nucleophilic addition by the side chain of glutamyl carboxyl oxygen atom takes places. On the other hand, the prolyl residues in PPECG can largely diminish the nucleophilic addition, resulting in a much lower efficiency of its E–C amide bond breaking. Distance analysis indicates that breaking the E–C amide bonds in the protonated γ -ECG, ECG, and PPECG ions could not occur without the assistance from the nucleophilic attack, highlighting an asynchronous collaborative process in the bond breakings.